Problem przekładu wykrzykników - Malinowska, Iwona (Przegląd Rusycystyczny, 2010)
THE PROBLEM OF TRANSLATION OF EXCLAMATIONS Summary Interjections very often turn up to be neglected by translators. The analysis aims to illustrate the various ways of translation of exclamations, including total omission of them. The aim of the article is to distinguish three groups according to different adequacy of translation. Examples show a very wide range of exclamations translation ways for a translator.The collected material for the research is taken from the original Russian and Polish liter-ary works that range from 19th to 21st century and their renderings. ПРОБЛЕМА ПЕРЕВОДА МЕЖДОМЕТИЙ Резюме Междометия очень часто находятся вне интереса переводчика. Задача настоящего анализа показать разнообразие перевода междометий, включая их упущение. Цель статьи — выделить три группы отличающиеся разным соответствием перевода. При-ведённые примеры показывают языковое пространство, по которому перемещается переводчик в поисках адекватного эквивалента.Материал для анализа составили избранные оригинальные произведения русской и польской литературы XIX, XX и XXI веков и их переводы.